ACADEMIC EXTRACURRICULAR PROGRAM MANAGEMENT IN A MADRASAH: A STUDY AT MIT AL ISHLAH GORONTALO - Miftha Huljannah; Novianty Djafri; Pupung Puspa Ardini; Mohamad Zubaidi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to describe the implementation, innovative value, and benefits of academic extracurricular programs at MIT Al Ishlah Gorontalo, covering supplementary classes in Mathematics, Languages, Qur’anic Studies, and Digital Literacy. A descriptive approach was employed, with data collected through observation, semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The findings indicate that all aspects of the activities from planning and implementation to evaluation, were carried out very effectively. Innovation is evident in the use of digital media (interactive videos, Qur’anic recitation murottal applications, and online quizzes) and the adoption of student-centered active learning methods. The novelty of this study lies in the integration of digital literacy and Islamic education within academic extracurricular activities in a madrasah ibtidaiyah. Practically, the program can serve as an integrated instructional model that strengthens students’ academic, spiritual, and technological competencies. Theoretically, the study contributes to broadening the understanding of contextual pedagogical innovation at the primary level and provides a foundation for developing madrasah curricula grounded in digital integration and Islamic character.